O cuidado da criança com câncer e o significado para o médico - Eliana Cavacami (2008)
How can doctors follow a child with cancer and its treatment process, which may go from the diagnosis to death, and not get involved? They can not. The subject of this research experiences an extreme human relationship, the cancer long treatment, the non-conformism with the child’s death, the transference to his/her condition of father and mother, the bond, the anguish on the search of objectiveness, the sensation of failure, reveal a painful work, very different form the one proclaimed in the traditional medical ideology of “do not get involve”, only keep a professional relationship when dealing with the child and the family. The cares prescribed in the set called palliative cares are the ones given to patients in death process, however intuitively. Everybody would feel relieved if there was a specialized team to take care of these terminal children and their families. The doctors of this research reflect what is socially stated, they experience the peculiar discomfort in the presence of those who are dying. Maybe we should speak more clearly and openly about death to be able to make the question: how to make the end, the human being farewell, as easy and pleasant as possible?